2021
DOI: 10.1016/j.heliyon.2021.e06650
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 molecular identification and clinical data analysis of associated risk factors from a COVID-19 testing laboratory of a coastal region in Bangladesh

Abstract: Background and Aim Outbreak of COVID-19 seems to have exacerbated across the globe, including Bangladesh. Scientific literature on the clinical data record of COVID-19 patients in Bangladesh is inadequate. Our study analyzes the clinical data of COVID-19 positive patients based on molecular identification and risk factor correlated with three variables (age, sex, residence) and COVID-19 prevalence in the four districts of Chattogram Division (Noakhali, Feni, Lakshmipur and Chandpur) with an aim to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Our analysis observed that 28.53% of COVID-19 patients were between the ages of 21 and 30, which may reflect the busiest part of life, such as when they had to go out for office or business and were primarily infected. A similar study reported that the highest percentage (51.80%) of SARS-CoV-2 infected patients were observed in the 20–40 years old age range [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our analysis observed that 28.53% of COVID-19 patients were between the ages of 21 and 30, which may reflect the busiest part of life, such as when they had to go out for office or business and were primarily infected. A similar study reported that the highest percentage (51.80%) of SARS-CoV-2 infected patients were observed in the 20–40 years old age range [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male domination in COVID-19 instances could be due to gender disparities in testing patients, women’s shyness, and a more active male population than the female population in our country, particularly in terms of jobs outside the home. A recent regional demographic investigation showed that males (56.8%) had been infected 13.6% higher than females (43.2%) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite of these measures,COVID-19 cases have spread to all 64 districts of Bangladesh 6 . The situation became more challenging due to noncompliance of people toward the universal protective measures, emergence of mutant variants of SARS-CoV-2and a second wave strike of COVID-19 in Bangladesh 9,10,11 . In Bangladesh, by 20 th September, 2021, about 1,542,683 confirmed COVID-19 cases with 27, 225 deaths were reported 5 .…”
Section: Introductionmentioning
confidence: 99%